Efek Antimikroba Kombinasi Nisin dengan Minyak Atsiri Curcuma pada Mikroorganisme Patogen dan Pembusuk Pangan - Rohula Utami; Ardhea Mustika Sari; Asri Nursiwi; Dyah Ayu Ashari (agriTECH, 2019)
Essential oil and nisin are natural compounds that have antimicrobial activity. Both compounds are generally recognized as safe (GRAS). The concentration of essential oil and nisin needed to inhibit the growth of microorganisms can be determined using the microdilution method. The combination of Curcuma xanthorrhiza, Curcuma longa, and Curcuma zedoaria (v/v) (0.25%; 0.5%; 1%; 2%; and 4%) with nisin (b/v) (62.5 IU; 125 IU; 250 IU; 500 IU; and 1000 IU) could inhibit the growth of Bacillus cereus FNCC 0057, Salmonella typhimurium FNCC 0050, Eschericia coli FNCC 0091, Staphylococcus aureus FNCC 0047, Pseudomonas fluorescens FNCC 0070, and Aspergillus niger FNCC 6080. In higher concentration, several combinations gave bacteriocidal effect on Bacillus cereus FNCC 0057, Salmonella typhimurium FNCC 0050, Eschericia coli FNCC 0091, and Pseudomonas fluorescens FNCC 0070. The combination of nisin with Curcuma xanthorrhiza, Curcuma longa, and Curcuma zedoaria showed synergistic activities in several target microorganisms.